Asta Gröting - das Wesen von x video works 1993-2023 - Krischke, Roland 1967-; Bell, Kirsty 1971-; Hervol, Anke 1969-; Sterngast, Tal 1972- (Spector Books, 2023)
Artist Asta Gröting has been working with the medium of moving images and sculpture for over three decades. She creates videos that explore the relationship between the human body and space, as well as the dynamics between humans and animals, and among animals themselves. Her films, performances, and sculptures all share a common focus on surfaces, aiming to uncover what lies beneath. Each of her works seems to be guided by a fundamental question: What is the essence of x? What defines the nature of a wolf or a dog? In her latest project, "Wolf and Dog," Asta Gröting introduces her exited Australian Shepherd dog, named Laika, to a relaxed wolf. Using an ultra-high-speed camera capable of capturing 1000 frames per second, she records the animals' shared feeding experience, then dramatically slows down the footage for projection onto a canvas. During the distribution of a piece of raw meat, the dog and the wolf peacefully coexist without conflict. Das Wesen von x is the central theme of an exhibition by the same name at the Lindenau Museum in Altenburg. In recognition of her work, the museum awarded Asta Gröting the Gerhard Altenbourg Prize in 2023
Impressum: Dieser Katalog erscheint anlässlich der Ausstellung "Asta Gröting. Das Wesen von x. Gerhard-Altenbourg-Preis 2023" im Prinzenpalais des Residenzschlosses Altenburg vom 20. August bis zum 31. Oktober 2023. Eine Sonderausstellung des Lindenau-Museums Altenburg
Keywords: Gröting, Asta -- 1961-; Geschichte 1993-2023; Videokunst; Kunst; Tier und Mensch; Katalog; Gerhard-Altenbourg-Preis; Ausstellungskatalog -- Prinzenpalais Altenburg -- 20.08.2023-31.10.2023 -- Altenburg, Thüringen; Bildband